Phosphorylated and Phosphomimicking Variants May Differ-A Case Study of 14-3-3 Protein - Kozeleková, Aneta; Náplavová, Alexandra; Brom, Tomáš; Gašparik, Norbert; Šimek, Jan; Houser, Josef; Hritz, Jozef (Frontiers in chemistry, 2022)
Protein phosphorylation is a critical mechanism that biology uses to govern cellular processes. To study the impact of phosphorylation on protein properties, a fully and specifically phosphorylated sample is required although not always achievable. Commonly, this issue is overcome by installing phosphomimicking mutations at the desired site of phosphorylation. 14-3-3 proteins are regulatory protein hubs that interact with hundreds of phosphorylated proteins and modulate their structure and activity. 14-3-3 protein function relies on its dimeric nature, which is controlled by Ser58 phosphorylation. However, incomplete Ser58 phosphorylation has obstructed the detailed study of its effect so far. In the present study, we describe the full and specific phosphorylation of 14-3-3ζ protein at Ser58 and we compare its characteristics with phosphomimicking mutants that have been used in the past (S58E/D). Our results show that in case of the 14-3-3 proteins, phosphomimicking mutations are not a sufficient replacement for phosphorylation. At physiological concentrations of 14-3-3ζ protein, the dimer-monomer equilibrium of phosphorylated protein is much more shifted towards monomers than that of the phosphomimicking mutants. The oligomeric state also influences protein properties such as thermodynamic stability and hydrophobicity. Moreover, phosphorylation changes the localization of 14-3-3ζ in HeLa and U251 human cancer cells. In summary, our study highlights that phosphomimicking mutations may not faithfully represent the effects of phosphorylation on the protein structure and function and that their use should be justified by comparing to the genuinely phosphorylated counterpart.
Keywords: phosphorylation; phosphomimicking mutation; 14-3-3; dissociation constant; oligomeric state